2008
DOI: 10.1021/es8016107
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Emissions during Cofiring of Sub-bituminous Coal and Biomass (Chicken Waste, Wood, Coffee Residue, and Tobacco Stalk) in a Laboratory-Scale Fluidized Bed Combustor

Abstract: Four types of biomass (chicken waste, wood pellets, coffee residue, and tobacco stalks) were cofired at 30 wt % with a U.S. sub-bituminous coal (Powder River Basin Coal) in a laboratory-scale fluidized bed combustor. A cyclone, followed by a quartz filter, was used for fly ash removal during tests. The temperatures of the cyclone and filter were controlled at 250 and 150 degrees C, respectively. Mercury speciation and emissions during cofiring were investigated using a semicontinuous mercury monitor, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Se and As have been defined as the markers of coal combustion (Galbreath and Zygarlicke, 2004;Reff et al, 2009), which was consistent with the only fuel used on the snack street. In addition, United States emission inventories of PM 2.5 trace elements revealed that coal combustion is the largest source of Hg (Cao et al, 2008;Reff et al, 2009). This explains that Hg was detected in the snack-street boiling only.…”
Section: Metalsmentioning
confidence: 99%
“…Se and As have been defined as the markers of coal combustion (Galbreath and Zygarlicke, 2004;Reff et al, 2009), which was consistent with the only fuel used on the snack street. In addition, United States emission inventories of PM 2.5 trace elements revealed that coal combustion is the largest source of Hg (Cao et al, 2008;Reff et al, 2009). This explains that Hg was detected in the snack-street boiling only.…”
Section: Metalsmentioning
confidence: 99%
“…To demonstrate the effectiveness of ReEF co-feeding with coal, a fluidized bed combustion (FBC) reactor was constructed, as shown in Figure schematic of the reactor and analytical system. A 5.0 cm outer-diameter alumina tube (99.8%, CoorsTek Inc.) was the main reactor inside a high temperature furnace, which can withstand temperatures up to 1650 °C.…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…heating value and moisture content), in order to reach high combustion efficiency and steady combustion characteristics [60][61]. A large number of papers discuss the co-incineration of MSW, RDF or biomass in existing coal fired FBCs for energy production [55,60,57,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. One of the advantages of this form of co-incineration is that the waste can be energetically valorized without high investment costs.…”
Section: General Design Strategymentioning
confidence: 99%
“…One of the advantages of this form of co-incineration is that the waste can be energetically valorized without high investment costs. Furthermore, as the carbon in MSW, RDF and biomass is up to 100% of biogenic origin, the net CO2 emission per unit of energy produced decreases compared to coal combustion [57,59,61,63,66,69,73]. Due to the different composition and combustion characteristics of MSW, RDF or biomass and coal (Table 4), the emission of certain pollutants during co-combustion can change significantly compared to pure coal combustion [77,64,60,69,72,[75][76].…”
Section: General Design Strategymentioning
confidence: 99%
See 1 more Smart Citation